The value of thermal management control strategies for battery energy storage in grid decarbonization: Issues and recommendations. (10th December 2020) - Hannan, M.A.; Al-Shetwi, AliQ.; Begum, R.A.; Young, S.E.; Hoque, M.M.; Ker, PinJern; Mansur, M.; Alzaareer, Khaled
Abstract: Deeply decarbonizing electricity production will likely require low-carbon sources that meet energy demand throughout days, years, and decades. Renewable energy sources (RES) are possible low-carbon options, but the intermittency of RES can limit their potential as viable options. Energy storage can be a solution to this problem by storing excess power from RES and providing power to the load when output power of RES is insufficient. To date, some researchers have investigated the effect of energy storage on power system operations and their environmental impacts. However, the effects of battery thermal management (BTM) controller on the decarbonization of power grid are not sufficiently covered. Thus, this paper presents a comprehensive review on the benefits of thermal management control strategies for battery energy storage in the effort towards decarbonizing the power sector. In this regard, the impacts of BTM controller and optimized controller approaches in terms of cooling, heating, operation, insulation, and the pros and cons of each are reviewed and discussed. Additionally, the impact of batteries, BTM controller, and renewable energy integration towards grid decarbonization are discussed. The advantages and disadvantages of various types of batteries concerning power density, normal temperature range, life-cycle, size, environmental impact, and toxic emission are also highlighted. This study also focuses on different issues and challenges related to the BTM as well as recommendations for future research. The review demonstrates that the existing BTM control techniques not only improve the batteries efficiency, but also reduce its environmental impacts. However, further enhancement of BTM control using optimization methods is needed to reduce greenhouse gas emissions. Besides, as the majority of current approaches are restricted to simulation analysis, experimental validation becomes necessary. In summary, this review will hopefully strengthen the efforts toward the development of clean power systems with less environmental impact toward grid decarbonization. Highlights: Battery energy storage can play a key role in decarbonizing the power sector. Battery thermal control is important for efficient operation with less carbon emission. A detailed investigation of the key issues and challenges of battery thermal controller. Experimental validation is needed for the impact of batteries in grid decarbonization. Selective suggestions for further development toward zero carbon emission.